A avaliação dos efeitos do programa de subvenção com base em indicadores de inovação: um estudo de caso da empresa Mogai Tecnologia de Informação - Kappel, Vítor Dias (2016)
The main purpose of this study is to evaluate the utility of traditional innovation indicators when the desire is to examine the effects of the policies promoted by FINEP to foster innovation through the grant instrument. Methodologically, a case study has been chosen in order to identify whether and how the captured results can be distorted or concealed by the traditional statistical method. For comparability purposes, these indicators were tested by contrast with the technological capability accumulation assessment. In conclusion, it was observed a weakness in the exclusive use of traditional innovation indicators due to the high existing risk of underreporting innovation. The technological capacity evaluation model proved suitable for being able to portray the accumulation of technical and managerial skills by the company. Finally, some remarks on possible improvements in the grant program based on the findings have been compiled in the conclusion.